Machine ebook A white space novel. - Bear, Elizabeth (White Space, 2020)
In this "spectacularly smart space opera" ( Publishers Weekly , starred review) set in the same universe as the critically acclaimed White Space series and perfect for fans of Karen Traviss and Ada Hoffman, a space station begins to unravel when a routine search and rescue mission returns after going dangerously awry. Meet Doctor Jens. She hasn't had a decent cup of coffee in fifteen years. Her workday begins when she jumps out of perfectly good space ships and continues with developing treatments for sick alien species she's never seen before. She loves her life. Even without the coffee. But Dr. Jens is about to discover an astonishing mystery: two ships, once ancient and one new, locked in a deadly embrace. The crew is suffering from an unknown ailment and the shipmind is trapped in an inadequate body, much of her memory pared away. Unfortunately, Dr. Jens can't resist a mystery and she begins doing some digging. She has no idea that she's about to discover horrifying and life-changing truths. Written in Elizabeth Bear's signature "rollicking, suspenseful, and sentimental" ( Publishers Weekly ) style, Machine is a fresh and electrifying space opera that you won't be able to put down.